Editorial: Observational studies in ADHD: the effects of switching to modified-release methylphenidate preparations on clinical outcomes and adherence - Rothenberger, Aribert (Springer-Verlag, 2011)
Patients with ADHD may have better adherence to treatment with modified-release methylphenidate (MPH-MR) formulations, which are taken once daily, compared with immediate-release (IR) formulations, which need to be taken several times a day. Data on long-term outcomes such as adherence may be lacking from randomised controlled trials as these are usually only short-term. Observational studies, if performed and reported appropriately, can provide valuable long-term data on such outcomes, as well as additional information on effectiveness and efficiency, from a real-life setting. By reviewing previous observational studies that have investigated switching treatment from MPH-IR to MPH-MR, results from a new, naturalistic observational study, the OBSEER study, are put into context. We conclude that, based on observational trial data, switching from MPH-IR to MPH-MR is a valid clinical approach, with the potential for improved clinical outcome and treatment adherence.